Maackiain Modulates miR-374a/GADD45A Axis to Inhibit Triple-Negative Breast Cancer Initiation and Progression - Fu Peng; Li Wang; Liang Xiong; Hailin Tang; Junrong Du; Cheng Peng (Frontiers Media S.A., 2022)
Breast cancer ranks as the leading cause of death in lethal malignancies among women worldwide, with a sharp increase of incidence since 2008. Triple negative breast cancer (TNBC) gives rise to the largest proportion in breast cancer-related deaths because of its aggressive growth and rapid metastasis. Hence, searching for promising targets and innovative approaches is indispensable for the TNBC treatment. Maackiain (MA), a natural compound with multiple biological activities, could be isolated from different Chinese herbs, such as Spatholobus suberectus and Sophora flavescens. It was the first time to report the anti-cancer effect of MA in TNBC. MA could suppress TNBC cell proliferation, foci formation, migration, and invasion. MA also exerted a significant inhibitory effect on tumor growth of TNBC. Furthermore, MA could induce apoptosis with an increase of GADD45α and a decrease of miR-374a. In contrast, overexpressing miR-374a would result in at least partly affecting the proapoptotic effect of MA and suppressing GADD45α stimulated by MA. These results reveal the anti-TNBC effect of MA in vitro and in vivo, providing evidence for its potential as a drug candidate utilized in TNBC therapy.